PELAKSANAAN PENYIDIKIAN TINDAK PIDANA PENGHINAAN TERHADAP AGAMA MELALUI KONTEN VIDEO MELALUI MEDIA SOSIAL - S, Laurensius Arliman (Ensiklopedia Sosial Review, 2019)
Indonesia is a country based on Pancasila, wherein the first principle states, "The One Godhead." So therefore all laws made by the state or government in the broadest sense, may not conflict with God's law, even more than that, every legal order that is made must be based on and intended to realize God's law. Freedom of speech, expression and freedom of the press are human rights, in a democratic country that is now Indonesia's choice, this right must be guaranteed. Besides the guarantee contained in the 1945 Constitution, the government also regulates it in the Criminal Code article 156, 156a and article 157. Indeed, in the Criminal Code there is no special chapter that regulates religious offense offenses or better known as religious offenses. However, the existence of these articles has proven that the government has regulated this religious offense. As well as Law Number 11 of 2008 concerning Information and Electronic Transactions.